Формування стратегії розвитку готельно-ресторанного бізнесу - Самчук, Анна Віталіївна; Samchuk, Anna Vitaliyivna (Ірпінь, 2023)
Дослідження стану стратегічного розвитку ресторану Козацька рада та визначення пропозицій щодо оптимізації стратегії розвитку даного закладу.

Research of the state of strategic development of the restaurant Kozatska Council and identification of proposals for optimizing the development strategy of this institution.
Formation of a strategy for the development of hotel and restaurant business
Keywords: стратегія; розвиток; готельно-ресторанний бізнес; війна; strategy; development; hotel and restaurant business; war